Bone and Development - Bronner, Felix; Farach-Carson, Mary C.; Roach, Helmtrud I. (Topics in Bone Biology, 2010)
This volume, the sixth in the series Topics in Bone Biology, presents the current knowledge of bone development, from growth to mineralization. Like previous volumes in this series, it embraces the important interaction between medical science and practice. Insights stemming from molecular and cellular events are applied to the clinical setting, providing a deeper understanding of bone development complications for the practicing clinician, whilst informing bone scientists of the advancements in their field and the wider applications of their research. Covering a diverse and current range of topics, including the genetic and epigenetic aspects of bone development, cell signaling in growth plate and bone development, evolution of bone proteins and the interrelationship between bone and other tissues, this volume provides a thorough look at bone development biology. The contributing authors to this volume are acknowledged authorities in their fields. In addition, the extensive lists of references point the reader to further information on any of the topics covered. Clinicians and researchers involved in child development and therapy will find this book a valuable addition to their libraries.